Polarization nano-tomography of tightly focused light landscapes by self-assembled monolayers - Eileen Otte (Nature Portfolio, 2019)
The realisation of 4D light fields, where longitudinal polarisation represents the fourth dimension, has been limited by the lack of appropriate analysis techniques. Here, the authors use interaction with self-assembled monolayers of fluorescent molecules, which allow for identification of non-paraxial light fields based on a single image frame.